DIGITAL NATIVES AND DIGITAL CHOICES: AN ANALYSIS OF ONLINE MEDIA’S INFLUENCE ON GEN-Z’S POLITICAL PREFERENCES IN THE 2024 NORTH SUMATRA GUBERNATORIAL ELECTION - Adi Pia; Elly Warnisyah; Aminuddin Aminuddin (UNIVERSITAS PAKUAN, 2025)
This study examines the contribution of online media to the political preferences of Generation Z (Gen-Z) in the 2024 North Sumatra Gubernatorial Election. Unlike previous generations, Gen-Z, as digital natives, exhibits patterns of political information consumption centered on visual and interactive digital platforms. Employing a qualitative methodology that incorporated questionnaires administered to 102 respondents and in-depth interviews with 25 participants, this study analyzes the formation process of Gen-Z’s political perceptions. The findings indicate that the Uses and Gratifications Theory is relevant in explaining the dominance of platforms such as TikTok and Instagram, which fulfill Gen-Z’s needs for edutainment and social interaction. Their process of political perception formation is strongly influenced by strategic Framing and political branding. Another key finding is the emergence of a hybrid participation model, where digital engagement triggers discussions in traditional social spaces. Gen-Z also demonstrates characteristics of Critical Digital Citizenship, exhibiting a critical stance toward disinformation and demanding data-driven content. This research provides theoretical contributions to the dynamics of digital political socialization and offers practical guidance for designing effective campaign strategies targeting young voters.